SPECIAL PHYSICAL PREPARATION OF LONG-DISTANCE RUNNING ATHLETES - Kh. X. Boymatov (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on determining the special physical fitness of long-distance running student-athletes based on pedagogic tests that represent their physical qualities. The study was conducted and the results after the study were covered. A comparative analysis of the obtained results with the results of a pedagogical study by leading scientists is given and is covered by the conclusions obtained at the end of the work.